Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/adma.202201277
|View full text |Cite
|
Sign up to set email alerts
|

Carrier‐Transport Mechanism in Organic Antiambipolar Transistors Unveiled by Operando Photoemission Electron Microscopy

Abstract: Figure 5. a-c) Illustrations and the energy-level alignments of AAT in the following

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…This indicates that electrons and holes recombine near the lateral interfaces of AATs. [ 32 ] Otherwise, the observed current should be larger than the calculated ones since no carrier transport from n–type to p–type, or p–type to n–type is considered in our calculations.…”
Section: Resultsmentioning
confidence: 96%
“…This indicates that electrons and holes recombine near the lateral interfaces of AATs. [ 32 ] Otherwise, the observed current should be larger than the calculated ones since no carrier transport from n–type to p–type, or p–type to n–type is considered in our calculations.…”
Section: Resultsmentioning
confidence: 96%
“…However, most studies have shown that the lateral heterointerface plays a determined role in OHJT. 39,40 Here, our results indicate that it may be achieved from devices with a single vertical organic heterointerface. In previous reports, ambipolar and depleted unipolar charge properties are ordinary from OHJT devices.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we revealed that the Λ‐shaped transfer curve of the AAT can be analyzed as the overlapped drain current in the saturation regions of the constituent transistors in the same analogy as that of the shoot‐through current (STC) in complementary metal–oxide semiconductor (CMOS) inverters. [ 28–30,41 ] The I D – V G curve of the AAT is generally given by the following equations: [ 38–40,43 ] ID,nbadbreak=W2LnμnCifalse(VGVth,nfalse)2\[ \begin{array}{*{20}{c}}{{I_{D,n}} = \frac{W}{{2{L_n}}}{\mu _n}{C_i}{{({V_G} - {V_{th,n}})}^2}}\end{array} \] ID,pbadbreak=W2LpμpCifalse(VDVG+Vth,pfalse)2\[ \begin{array}{*{20}{c}}{{I_{D,p}} = \frac{W}{{2{L_p}}}{\mu _p}{C_i}{{({V_D} - {V_G} + {V_{th,p}})}^2}}\end{array} \] where L n and L p are the effective channel lengths of the PTCDI‐C8 and α‐6T channels, respectively (here, 20 and 30 µm for the PTCDI‐C8 and α‐6T channels, respectively, given the p–n‐stacked layers with 35 µm width), W is the common channel width (400 µm), and C i is the capacitance of the insulator per unit area (73.5 nF cm −1 ). Moreover, I D,n , µ n , and V th,n are the PTCDI‐C8 transistor's I D in the saturation region, electron carrier mobility, and threshold voltage, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The carrier transport mechanisms are basically the same as those proposed by PEEM measurements in our previous work. [ 43 ] The HOMO and LUMO energy levels of the PTCDI‐C8 and α‐6T layers and the Fermi level of Au electrodes were evaluated in that work. When V G is < V on , holes are accumulated in the α‐6T channel due to the effective gate voltage ( V D − V G ) (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%